LEVEL OF AWARENESS AND PERCEPTION OF SECTORAL GROUPS ON ECONOMIC, PHYSICAL, PSYCHOLOGICAL, AND SEXUAL ABUSES COMMITTED BY THE PERPETRATORS UNDER RA 9262: OR VIOLENCE AGAINST WOMEN AND CHILDREN ACT - Gaffud, Milagros N.; Luna, Gabriel L. (International Journal of Psychosocial Rehabilitation, 2020)
The research determined the level of awareness and perception of sectoral groups on violence against women and children act or RA 9262, particularly on aspects of economic, physical, psychological, and sexual abuses committed by the perpetrators to their wife and children which served as basis for intensified information, education and communication program. The study employed the descriptive research, involving the 460 respondents. Data were analyzed using the frequency percentage, arithmetic mean, F-test, Chi square test, and Correlation Coefficient r – test. Research findings concluded that majority of the respondents were 40 years old and below, female, married, affiliated to Roman Catholics, college graduates, employed as office workers, teachers and barangay officials, with monthly income of 10,000 and below; and lived in the rural areas of Tumauini, Isabela. Respondents expressed full awareness and strong agreement on economic, physical, psychological, and sexual abuses, with acts as very seriously committed by husbands to their wives. Those male respondents, young, single, Roman Catholics, with higher education, employed, low monthly income, and living in the rural areas tended to become more knowledgeable of the economic, physical, psychological, and sexual abuses as provisions of RA 9262 than their counterpart. Male respondents, young, single, Roman Catholics, with high education, employed, with low monthly income, and living in the rural areas tended to show stronger agreement on the provisions of economic, physical, psychological, and sexual abuses of RA 9262 as very serious acts of violence committed by husbands against women and their children. The more that the sectoral groups are knowledgeable of the economic, physical, psychological, and sexual abuses as provisions of RA 9262, the stronger is the perception on the provisions as very serious acts of violence committed by husbands against women and their children.